(untitled) (International Journal of Management, Public Policy and Research, 2025)
The agricultural sector plays a critical role in ensuring food security, employment, and economic stability, yet rural farmers face significant challenges, particularly limited access to financial services. This study explores the potential of digital financial inclusion to empower farmers and enhance agricultural productivity. Digital financial inclusion refers to using digital tools such as mobile banking, digital wallets, and online lending platforms to deliver financial services to underserved populations. Despite its benefits, including improved access to credit, savings, and insurance, adoption among farmers is hindered by inadequate digital literacy, poor infrastructure, and cultural resistance. This research, conducted among 100 farmers in Palaj, Gandhinagar, reveals that while mobile banking apps are widely used, barriers such as security concerns and lack of awareness persist. The study highlights the role of government programs and local organizations in promoting digital financial literacy and emphasizes the need for targeted educational initiatives, improved infrastructure, and tailored financial products. Findings suggest that digital financial tools enhance financial security and productivity, offering long-term socioeconomic benefits. However, challenges such as mistrust of digital systems and insufficient internet access remain significant. Addressing these issues will enable broader financial inclusion, supporting sustainable economic growth and improving the livelihoods of rural farming communities.